A generalization of modified Bourget”™s functions - Quero, Sandra; Galué, Leda (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we present a generalization of modified Bourget”™s functions and important properties of themselves, such as: generating function and recurrence relations. Further a differential equation of fourth order satisfied by the modified Bourget”™s functions in generalized way is built. The results given by N. Hayek and E. R. Negrin in 1989 are particular cases of these here obtained.